1999
DOI: 10.1136/hrt.82.3.365
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic control of the cerebral circulation during normal and impaired peripheral circulatory control

Abstract: Objective-To determine whether oscillations in the cerebrovascular circulation undergo autonomic modulation in the same way as cardiovascular oscillations. Design-Cardiovascular and cerebrovascular oscillations were monitored at rest and during sympathetic stimulation (head up tilt). The association with and transmission of the oscillations in the sympathetic (low frequency, LF) and respiratory (high frequency, HF) bands was assessed. Subjects-13 healthy volunteers, 10 subjects with vasovagal syncope, and 12 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 35 publications
8
79
3
Order By: Relevance
“…The phase shift results in our study are at slight variance with the results reported by Cencetti et al [23]. During head-up tilt, Cencetti et al observed a significant reduction in phase shift in their controls [23].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The phase shift results in our study are at slight variance with the results reported by Cencetti et al [23]. During head-up tilt, Cencetti et al observed a significant reduction in phase shift in their controls [23].…”
Section: Discussioncontrasting
confidence: 57%
“…During head-up tilt, Cencetti et al observed a significant reduction in phase shift in their controls [23]. This shortening of phase shift was ascribed to sympathetic activation and subsequent sympathetically mediated vessel stiffening [23].…”
Section: Discussionmentioning
confidence: 99%
“…This 'stretching' could then reverse the glycation-related collagen crosslinking that is responsible for reduced arterial compliance. 7 Increases in the amount of collegen in the arterial wall, hypertrophy of the smooth muscle present in arterial walls and dysfunction of the endothelium have also been hypothesized to underlie increases in arterial stiffness in older adults with hypertension, 7 although the role of exercise in reversing these mechanisms remains uncertain.…”
Section: S Edentary Behaviors Have a Well-establishedmentioning
confidence: 99%
“…20 It has been hypothesized that pulsatile stretching of collagen fibers during aerobic exercise could break the collagen links and result in decreased arterial stiffness. 21 However, the impact of aerobic exercise on arterial stiffness in diabetic patients is still uncertain. A 3-month study with 36 elderly diabetic patients randomized to aerobic or anaerobic exercise showed a reduction in arterial stiffness in the aerobic group, 8 whereas another study with 50 patients randomized to exercise training or standard treatment did not show any change in aortic stiffness after a 24-month program.…”
Section: Discussionmentioning
confidence: 99%